A new earthworm genus with two new species (Clitellata, Megascolecidae) from the Western Ghats mountain ranges of south-western peninsular India - Narayanan, S. Prasanth; Thomas, A.p.; Julka, J.m. (Zootaxa, 2025)
A new megascolecid earthworm genus, Aiyeriella Narayanan & Julka gen. nov., is established from the Western Ghats biodiversity hotspot of India, with two new species, namely, A. quadritheca Narayanan & Julka, sp. nov., and A. longiprostata Narayanan & Julka, sp. nov. Material of the new genus and species were collected from the three southernmost districts of Kerala state, in the south-western portion of peninsular India. The present new genus can be distinguished from other related Indomalayan megascolecid genera by the presence of combined male and prostatic pores paired in seminal grooves on segment 18, with a single well-developed oesophageal gizzard in segment 5, penial setae, calciferous glands, intestinal caeca, and typhlosole absent, meronephric throughout the body, 10–14 in transverse bands of micromeronephridia behind clitellum and prostates tubuloracemose, paired, elongated, and strap-shaped.